PENGARUH PENERAPAN MEDIA AUDIO VISUAL TERHADAP AKTIVITAS BELAJAR SISWA KELAS VIII DI MTs DARUN NAJAH OGAN ILIR - Ikke Yumelda; Fajri Ismail; Herman Zaini (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
This study aims to determine the increase in learning activities of control class and experimental class students who are applied audio visual compact disc (CD) learning media on the subject of Islamic cultural history class VIII at MTs Darun Najah Ogan Ilir. This type of research is quantitative research with experimental research methods (experimental method) using research design Tru Esperimental design. The data sources consist of primary and secondary data sources. Then the population is 82 students and the sample is 30 students. Data collection techniques are observation, tests, and documentation. Then the data analysis technique used the